2014
DOI: 10.1002/jssc.201400919
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of florfenicol with its metabolite based on modified quick, easy, cheap, effective, rugged, and safe sample pretreatment and evaluation of their degradation behavior in agricultural soils

Abstract: A simple and simultaneous method for the determination of florfenicol and its metabolite florfenicol amine in agricultural soils using modified quick, easy, cheap, effective, rugged, and safe sample pretreatment and reversed-phase high-performance liquid chromatography with tandem mass spectrometry is presented. Florfenicol and its metabolite florfenicol amine residues in agricultural soils were extracted with alkalized acetonitrile and an aliquot was cleaned up with Si(CH2)3NH(CH2)2NH2 and C18 sorbent, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…confirmed that the biologically active of florfenicol could remain long-time in soils36 and exert a selective pressure for resistance genes in the environment. In addition, a previous study34 looking at the relative robustness of florfenicol showed that the half-life of florfenicol in native soil is approximately 8 days and the degradation behavior of florfenicol in the soils was connected with the activity of microbe community. Considering the rapid degradation rate of florfenicol in native soils, it is possible that the detection of florfenicol in these soil samples depend on whether the sampling sites were irrigated with florfenicol contaminated manure or not in recent days.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…confirmed that the biologically active of florfenicol could remain long-time in soils36 and exert a selective pressure for resistance genes in the environment. In addition, a previous study34 looking at the relative robustness of florfenicol showed that the half-life of florfenicol in native soil is approximately 8 days and the degradation behavior of florfenicol in the soils was connected with the activity of microbe community. Considering the rapid degradation rate of florfenicol in native soils, it is possible that the detection of florfenicol in these soil samples depend on whether the sampling sites were irrigated with florfenicol contaminated manure or not in recent days.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, a rapid UPLC-MS/MS method with a lower LOD (0.08 ng g −1 ) and LOQ (0.25 ng g −1 ) values compared with previous methods3435 was established to determine the levels of florfenicol in soil samples. To date, a number of reports have described the detection of various antibiotic residues, including tetracyclines, (fluoro)quinolones, and sulfonamides, in agricultural soils3031.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the uptake of antibiotics by edible plants has been reported [6,15]. Later, florfenicol and its metabolites (florfenicol amines) were determined in soil using an original QuEChERS method and LC-MS/MS [16]. Clearly, none of the methodologies above used acetate-buffered QuEChERS or were able to quantify ceftiofur, clopidol, monensin, salinomycin, tiamulin, and tylosin in soil samples.…”
Section: Introductionmentioning
confidence: 99%
“…The fate of antimicrobials discharged into the environment is complex, as the degree of antimicrobial adsorption in soil depends on the antimicrobial type, soil properties [20], and microbial processes [21]. For example, the amount of tetracyclines present in pig manure could be reduced by composting, but soil fertilized with the compost still contains up to 776.1 µg/kg and is considered sufficient for an ARB-selective effect [22].…”
Section: Impact Of Veterinary Antimicrobials On Arb and Args And Thementioning
confidence: 99%